Persepsi Rekognisi Toleransi Keberagaman Siswa dalam Upaya Penerapan Pendidikan Multikultural di SDN Jatinegara Kaum 11 Pagi: Perceptions of Tolerance Recognition of Student Diversity in Efforts to Implement Multicultural Education at SDN Jatinegara Kaum 11 Pagi - Nawawi, Muhammad Azhar; Maksum, Arifin; Nurhasanah, Nina (Anterior Jurnal, 2025)
This research examines the perception of tolerance of student diversity at SDN Jatinegara Kaum 11 Pagi. Tolerance of diversity is one form of character that reflects human rights values in it. As social beings, students do not live with the same cultural uniformity as themselves, but in the school environment students encounter diversity as plural and multicultural individuals. For this reason, it is very important to instill the character of tolerance of diversity in students in elementary schools as a provision for living in a diverse social environment through the application of multicultural-based education with a recognition theory approach from Axel Honneth. This research uses a quantitative approach. Data collection used purposive sampling research techniques in the form of a questionnaire with a Likert scale model. Data collection was conducted online through the GoogleForm platform in September-November, Data analysis used descriptive statistical techniques. The results of the research conducted show that students' tolerance for diversity has increased at SDN Jatinegara Kaum 11 Pagi, from the percentage of data on the perception of students' tolerance for diversity has increased positively with data on indicators of aspects of peace with the whole statement showing results of 46.5%, on data indicators of aspects of respect for differences and individuals with the whole statement showing results of 43.2%, and on data indicators of aspects of awareness with the whole statement.